The effect of various traditional Indonesian face powders on the prevention of UVA and UVB skin pigmentation. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Key words: traditional face powders - sunscreen - UVA - UVB - pigmentation.